Penentuan Derajat Polimerisasi Inulin dari Umbi Dahlia (dahlia sp.) Menggunakan Metode HPLC Dengan Detektor RID - Basultan Hidayat; Minda Azhar; Iryani Iryani; Hary Sanjaya (Jurnal Periodic Jurusan Kimia UNP, 2021)
The degree of polymerization (DP) of inulin plays important rolein inulin utilization.This study aims to determine and compare DP of inulin from dahlia tubers that wereextracted in fresh and extracted after storaging in 15 days.Extraction of inulin is carried out based on its solubility in hot water.DP of inulin was measured using a High Performance Liquid Chromatography (HPLC) instrument with variety of measurement conditions. HPLC with RID detector, Hi-plex H Column, 100% aquabidest mobile phase, flow rate of 0.6 ml / minute, and injection volume of 20 µl gave the best measurement results. Dahlia tubers extracted in fresh produce fructose content 1.02%, while extracted after storaging in 15 days produce fructose content 1.71%.Hence, DP of inulin from dahlia tubers extracted in fresh is greater than DP of inulin from dahlia tubers extracted after storaging in 15 days.